Fish consumption is inversely associated with type 2 diabetes in Manitoba First Nations communities - Lesya Marushka; Malek Batal; Donald Sharp; Harold Schwartz; Amy Ing; Karen Fediuk; Andrew Black; Constantine Tikhonov; Hing Man Chan (Canadian Science Publishing, 2017)
Consumption of fish and n-3 fatty acids (n-3 FAs) has been postulated to prevent type 2 diabetes (T2D). Objective: To explore the association between self-reported T2D and fish consumption, dietary n-3 FAs, and persistent organic pollutants (POP) intake in a regionally representative sample of First Nations (FNs) in Manitoba. Design: Data from the cross-sectional First Nations Food, Nutrition and Environment Study (FNFNES) collected from 706 members of 8 Manitoba FNs in 2010 were used. Household interviews were used to collect social and lifestyle data. The consumption of fish was estimated using a traditional food frequency questionnaire. Fish samples were analyzed for the presence of POP. Multiple logistic regression models adjusted for potential risk factors for T2D were developed. Results: A negative, dose-response relationship was found between fish intake and self-reported T2D. Fish consumptions of 2-3 portions per month and ≥1/week were inversely associated with T2D with odds ratio (OR) values of 0.51 (95% CI: 0.28-0.91) and 0.40 (95% CI: 0.19-0.82), respectively, compared with no fish intake. Similarly, intake of n-3 FAs was negatively associated with T2D (OR = 0.48 (95% CI: 0.30-0.77). Dietary POP intake was not associated with T2D. Conclusion: These findings suggest that the consumption of traditionally harvested fish may have a beneficial effect on T2D in Manitoba FNs.